(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2022)
In the interlevel classrooms of Rural Grouped Schools, students from different grades of the same or different educational stage coexist and learn together. The aim of this work are: (a) to determinate the advantages and disadvantages of collaborative learning in interlevel classrooms; (b) to evaluate the incidence of self-regulated learning in interlevel classroom. After a case study, the following results were obtained: (a) collaborative learning has more advantages than disadvantages in this type of classroom; (b) self-regulated learning in the interlevel classrooms promotes student autonomy, although in requires techniques and instruments that support and facilitate this process for students.